2017
DOI: 10.1080/19932820.2017.1283162
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic cardiomyopathy: is there any correlation between the stage of cardiac impairment and the severity of liver disease?

Abstract: Cirrhotic cardiomyopathy is associated with poor prognosis and risk of acute heart failure after liver transplantation or interventional procedures. We aimed to assess the relationship between the severity of cardiac impairment and hepatic disease. Eighty patients and eighty controls underwent echocardiography, tissue Doppler imaging and speckle tracking measures. We assess the correlation between echocardiographic parameters and Child and MELD scores. Systolic parameters function (s wave, p < 0.001) and globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 32 publications
6
46
0
1
Order By: Relevance
“…In most studies controls had no cardiac dysfunction but in two studies[35,25] 4.7% (overall 15 out of 318) controls were diagnosed with LVDD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most studies controls had no cardiac dysfunction but in two studies[35,25] 4.7% (overall 15 out of 318) controls were diagnosed with LVDD.…”
Section: Resultsmentioning
confidence: 99%
“…In our systemic analysis the data about LVDD prevalence in cirrhotic patients depending on Child-Pugh classes was available from 5 studies (365 patients overall)[16,24,25,32,34] and only Bhuin et al[16] found LVDD being associated with severity of liver cirrhosis ( P < 0.005). Other four studies did not find any difference in the severity of LVDD among Child classes[24,25,32,34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations